Probing China's soul religion, politics, and protest in the People's Republic - Ching, Julia (Harper & Row, 1990)
The author probes the soul of China starting with the formation of the Communist Party in Shanghai in 1921. She distinguishes clearly between the legacy of Chinese tradition and the innovations of Marxism. Outlines the power struggles under Mai Zedong and Deng Xiaoping, the causes and effects of the Cultural Revolution, the nature of both dissent and its repression in China and the student protests, and the feasibility of Chinese democracy.